CHD2-epilepsy: Polygraphic documentation of self-induced seizures due to fixation-off sensitivity. (April 2018) - Caputo, Davide; Trivisano, Marina; Vigevano, Federico; Fusco, Lucia
Abstract: CHD2 gene has been described in association with different types of childhood myoclonic epilepsy and is emerging as a gene involved in photosensitivity alone or combined with epilepsy. Recent studies suggest that CHD2 could be responsible for a proper phenotype characterized by infantile-onset generalized epilepsy, intellectual disability, and photosensitivity and in particular with self-induced seizures. We report the case of a child with CHD2 mutation and mild developmental impairment that since the age of 3 years started with myoclonic seizures apparently well responding to antiepileptic drugs and that subsequently developed intractable self-induced seizures. Through an accurate Video-EEG polygraphic analysis, we demonstrated that seizures are related to an abnormal increase of epileptiform activity after eye-closure or loss of fixation as observed in the Fixation-Off Sensitivity (FOS) phenomenon. In conclusion our study adds relevant features of the CHD2-epilepsy phenotype and confirms that CHD2 mutations produce a distinctive form of myoclonic epilepsy with visual-sensitive seizures.